Maano? a qualitative study on the Filipino Tagasalo experiences and emotions - Olaya, Honey Joy G.; Bayani, Kylla Fatima C.; Catenza, Ilys Mae (2023)
The concept of the Tagasalo was introduced by Carandang (1987) and studied by Udarbe (2001). This study explored the experiences and emotions of the Filipino Tagasalo. Specifically, this study delved on the participant's experiences and understanding of their role in the family, their emotions and how they experienced and regulated these emotions. The research utilized a qualitative approach with a descriptive phenomenological study design to describe and explain their tagasalo experiences. A semi-structured interview was conducted to 10 Waray-speaker participants residing in the Philippines. The data gathered was analyzed through thematic analysis (Braun & Clarke, 2006) which resulted into four clusters of themes namely: the budding tagasalo; tagasalo roles and responsibilities; tagasalo issues and challenges; and the emotions and emotion regulation strategies. Findings revealed that the Filipino Tagasalo's family relationship and deeply-held family values influence how they find the role heavy and difficult and their unconditional love for the family is their motivation in assuming their tagasalo responsibilities. The study also found that the tagasalo participants experience both negative emotions (e.g., forlorn and tiredness) and positive emotions (e.g., love happiness, and enjoyment) when executing their role. Six emotion regulation strategies were common among the tagasalo participants, these were: (1) cognitive restructuring, (2) problem confrontation, (3) avoidance, (4) emotion and action incongruence, (5) crying and (6) social sharing of emotions.